Face to Face wiith Denis Marleau / Face à Face avec Denis Marleau, Ottawa, 29 November, 2000 - Ruprecht, Alvina (Theatre Research in Canada / Recherches théâtrales au Canada, 2001)
In the Spring of 2001, Denis Marleau, artistic director and founder of the Théâtre Ubu (Montreal), became artistic director of French theatre at the National Arts Centre, after performing his plays on all the most important European stages. This interview, the first one he gave upon assuming his new position in Ottawa, tries to establish the general orientation of Marleau’s future artistic choices in relation to his own creative work and the programmes he will present at the National Arts Centre (NAC). The interview moves towards Marleau’s own research on Modernity through theatre practice, especially as it appears in Maeterlinck’s symbolist theatre. He also discusses his staging of Catoblépas, a performance based on a text by Gaëtan Soucy that was presented at the "Theatre Festival of the Americas" in Montreal, May 2001. Après avoir fréquenté les théâtres les plus prestigieux de l’Europe, Denis Marleau, directeur artistique et fondateur du Théâtre Ubu (Montréal), est devenu directeur artistique du Théâtre français au Centre national des Arts (CNA). Cet entretien, le premier qu’il ait accordé depuis qu’il a assumé son nouveau poste, essaie de cerner l’orientation possible de ses choix artistiques, choix qui auront des répercussions importantes à la fois sur la programmation du CNA. et sur ses propres recherches scéniques. La discussion met en relief l’intérêt que porte Marleau sur la Modernité au théâtre, surtout en tant que manifestation de l’esthétique symboliste don’t l’oeuvre de Maurice Maeterlinck serait le représentant le plus intéressant. Il s’agit également de Catoblépas, une oeuvre réalisée à partir du texte de Gaëtan Soucy, présentée au "Festival des Amériques" à Montréal en mai 2001.